Novas perspectivas para a comercialização de produtos agroecológicos: um estudo de caso em Hojarasca Carmen de Viboral, Colômbia - Souza, Gabriela Ferreira de (Universidade Federal de São Carlos, 2014)
The systematization of an agroecological transition and the local-regional markets is extremely important to build knowledge on this area. This systematization enable people, who are involved on this work, to have more precise information, increasing the success in the whole process. The present study systematizes a marketing initiative of agroecological products in Carmen de Viboral, Colombian, Antioquia department, from its agroecological transition, the development, until the concretion and stability of its initiative. The methodological approach was based on a notorious local peasant´s narrative, named Carlos Osorio, it was analyzed the reasons that induced him to work with agroecology, the emergence of a marketing channel, and the meeting with consumers, was take into consideration. It was also observed his present structural and organizational aspects; distinguishing its consumers and the strategies that he used to establish the initiative. It makes use of a semi-structured interview, a questionnaire and Diagnostic Rural Participative. The theoretical framework used was Van der Ploeg (2008) and the Stiologia Zaoual theory (2006). This case study shows the reasons that induced a person to change radically not only his life, but the relation he has taking care of the soil, agriculture, and also their lives. The peasant was succeed of closing a cycle, from its production until finding an autonomous commercialization channel for his agroecological products using mechanisms of symmetric reciprocity; enhancing important values, that our society relativized or even forget about, such as, confidence, solidarity, ethics, love, honesty and long-term planning.
Keywords: Agroecologia; Mercado agroecológico; Iniciativa local; Transição agroecológica; Local initiatives; Peasant markets; Agroecology; Agroecological transition; CIENCIAS AGRARIAS